Implementasi Pengembangan Kurikulum PAI Berbasis Pendidikan Karakter - Alqori Gustiansyah; Salmaini Yeli (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2022)
Education is one of the important elements in educating the nation's generation that must be managed properly in order to improve the nation's morals. This is because the essence of education is not just teaching, but also educating morals. This research is a library research that uses secondary data obtained through scientific articles and other relevant documents. The purpose of this research is to explain the implementation of PAI development which is oriented towards character education. The implementation of character values in PAI learning includes religious, integrity, character, discipline, responsibility, great interest in science, curiosity, confidence, respect for style, obedient to social rules, healthy lifestyle, aware between right and abigation, good job, and pay attention. To optimize the implementation of character education, it must receive support from all parties, especially teachers and parents who have a very important role.